ANALISIS PERENCANAAN PELAKSANAAN DAN PENGAWASAN DALAM PENGELOLAAN KEUANGAN DAERAH PADA DINAS KESEHATAN KOTA PEKANBARU TAHUN 2012-2014 - Suharti Suharti; Robiathul Hasyimah (Procuratio : Jurnal Ilmiah Manajemen, 2016)
This research thesis motivated by Planning and control is done by the Department of Sanitation Pekanbaru, so the authors feel compelled to disclose how the effect of the planning and control of region finance management at the department of sanitation Pekanbaru. This research aims to identify and analyze the responses with the effect of planning and control and also for know simultaneously or partially on Region Finance Management at the Department of Sanitation Pekanbaru. The method for this research using a descriptive method and sign test with a sample of people. The document collect technique used was a questionnaire. After proced the document and analysis it can be concluded that there is significant influence between planning and control of region finance management. From the test result obtained document are normaly distributed there is free aoutocorrelation, heteroscedasticity and multicollinearity. The sign test for variabel controling of not significant result value is 0,8554 < 0,95. It is mean the variabel not significant. Tujuan penelitian ini adalah menganalisis pengelolaan dalam perencanaan, pelaksanaan dan pengawasan Pada Dinas Kesehatan Kota pekanbaru. Penelitian ini bertujuan untuk mengetahui mengetahui perencanaan, pelaksanaan dan pengawasan baik secara simultan maupun secara persial Dalam Pengelolaan Keuangan Daerah Dinas Kesehatan Kota Pekanbaru Tahun 2012-2014. Metode yang digunakan dalam penelitian ini yaitu dengan menggunakan metode deskriptif dan uji tanda (sign test). Dari hasil penelitian diketahui bahwa hanya variabel pengawasan yang tidak signifikan atau belum efektif dikarenakan nilai probabilitas sebesar 0,8554 < dari taraf nyata sebesar 0,95 dalam pengelolaan keuangan Pada Dinas Kesehatan Kota pekanbaru.